Telemedicine and COVID-19 Pandemic: Valuable Lessons for Future Implementations - Urfa Khairatun Hisan; Irianto Irianto; Ihwan Ghazali; Muhammad Miftahul Amri (Journal of Novel Engineering Science and Technology, 2022)
Telemedicine has gained significant momentum during the pandemic. Telemedicine offers a way for people to access medical care without having to physically visit a healthcare facility, which can be especially important when in-person visits may not be safe due to a highly contagious virus. One major benefit of telemedicine is that it allows for the continuation of healthcare services while also helping to reduce the spread of COVID-19. By providing virtual consultations and treatments, telemedicine helps to limit the number of in-person visits. This is critical to reduce the risk of exposure to the virus and prevent healthcare facilities from becoming overwhelmed. Telemedicine has also helped to address some challenges that have arisen as a result of the pandemic. For instance, by using telemedicine, healthcare providers can reduce the need for PPE and maintain a safe distance while still providing necessary medical care. Despite the many benefits, there are also some challenges and limitations. For example, not everyone has access to the necessary resource to participate in telemedicine. Additionally, some medical procedures and treatments may not be suitable for telemedicine, requiring in-person visits. Moreover, it is important to consider the ethical issues that it raises and to work toward solutions that address these concerns. This can involve measures such as ensuring that telemedicine is available and accessible to all who need it, protecting patient privacy and confidentiality, and ensuring that telemedicine is used in a way that provides the highest quality and most appropriate care for patients.